EFFECT OF LONG TERM ADMINISTRATION OF CARROT ROOTS (Daucus carota) ON SOME CYTOGENETIC PARAMETERS IN WHITE MICE - Ilham A. Khalaf (Mesopotamia Journal of Agriculture)
The effect of long term administration of carrot roots (2 months) on some cytogenetic parameters in bone marrow cells of white mice was studied , these included , mitotic index (MI) , micronuclei formation (Mn ) , and chromosomal aberrations (Ch . ab .) of different types . In addition the effect was studied in germ cells (Sperms) by scoring the number and types of sperm – head abnormalities in comparison of the effect induced by cyclophosphamide (Cp) . Results showed that Cp reduced the MI to about 44 % of the normal value (6.84), administration of carrot before the drug (Ca/Cp) raised the index to 74 % of the normal value , while administration of carrot with the drug (Ca+Cp) restored 92.4 % , and administration of Cp followed by carrot (Cp/Ca) restored 88.9 % of the normal value . Cp induced Mn to about 17 times of the baseline value 1.06 .The different treatments with carrot reduced the Mn to 3.8 – 6.7 times the natural values , and the (Ca/Cp ) treatment was the best . Cp treatment for long time raised the Ch .ab. to about 10 times the natural value 1.62 , these values reduced upon administration of carrot to about 24.5 – 29.8 % of the positive control 17 , and such effect extended to the types of Ch. ab. except that of dicentric chromosomes which persisted with high values , but it was lower than the positive control with statistical difference (P<0.01) . The drug increased the sperm – head abnormalities to about 18 times the natural background 1.15 . Different treatments of carrot reduced the level of abnormalities with significant differences compared to positive control (P<0.01) , but the abnormalities were higher than the negative control with statistical difference (P<0.01) , these results were reflected on the types of abnormalities .